IN VITRO PROPAGATION COLLA AROMATIC ROXB : https://doi.org/10.69692/SUJMRD090125 - ANOUSACK, Phonekeo; THAMMAVONG, Khamko; SALITHXAY, Timnoy; CHATHAOKALOR , Daovang; CHANTHAKHOUN , Vongpasith (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This experiment was tested the propagation of Colla aromatica Roxb with tissue culture, the study objective to study of propagation possibility of Colla aromatica Roxb (Homalomena aromatica Schott. Araceae), this study found the possibility of disinfecting Colla aromatica Roxb using sodium hypochlorite solution in contains of 15 and 20 for 5 and 10 minutes, bacteria contamination was 0%, fungal contamination was 14.29%, the survival rate was 85.71% At the same time without Chemicals stimulate growth of plant, can't cause callus form callus in the case . After rearing young shoots of for 30 days, feeding Benzyl Adenine Pure (BAP) at a contains of 3 mg/l combined with Naphthalene Acetic Acid (NAA) at a contain of 1 mg/l, there was a high number of shoots 1.88 shoots, but at the same time, giving NAA only was found to be statistically different. after culture the shoots in Agar media for 60 days, it was found that the result of giving NAA combined with BAP for the elongation of the shoot is not statistically different, from the observation that giving NAA combined with BAP with a high contains, will have the characteristics of the shoot elongation that is better than giving NAA combined with low contains